2004
DOI: 10.1063/1.1830683
|View full text |Cite
|
Sign up to set email alerts
|

Temperature profile and pressure effect on the growth of silicon nanowires

Abstract: The excess temperature at the tip of silicon nanowires during their growth is calculated and found to be generally low. Therefore the special adhesive property of the tip cannot be explained by the excess temperature. The effect of surface tension is analyzed and we found that it cannot cause a significant lowering of melting point at the tip. Based on the charge-assisted mechanism proposed earlier by us, we note that charge accumulation at the tip results in a strong negative pressure. We propose that this is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…They reported that the electric charge accumulated at the tip of the nanowires produces a strong electric field and attracts most of the SiO vapor, forcing it to land on the tip. 4,37 Such an electrostatic of charged nanoparticles might result in the one-dimensional growth of nanowires. [38][39][40] Both positively and negatively charged nanoparticles are believed to participate in the growth of nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the electric charge accumulated at the tip of the nanowires produces a strong electric field and attracts most of the SiO vapor, forcing it to land on the tip. 4,37 Such an electrostatic of charged nanoparticles might result in the one-dimensional growth of nanowires. [38][39][40] Both positively and negatively charged nanoparticles are believed to participate in the growth of nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…This electrostatic energy might be related to the fact that the catalytic metal particles should be placed on an insulating substrate, such as quartz or alumina. Cheng and Cheung , proposed a charge-assisted mechanism to explain the growth of Si nanowires without catalytic metal particles. They reported that the electric charge accumulated at the tip of the nanowires produces a strong electric field and attracts most of the SiO vapor, forcing it to land on the tip. , Such an electrostatic interaction of charged nanoparticles might result in the one-dimensional growth of nanowires. Both positively and negatively charged nanoparticles are believed to participate in the growth of nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…∆f stands for the change of the in-plane surface stress coming from the H-F forces on the charged surfaces, linearly varied with the interfacial charge density demonstrated by the experimental measurement. In addition, the surfaces usually suffer from the negative pressure when there exists the electric field on the surfaces [20,21]. Based on the interfacial constitutive relation for the interface of the electrode [13], the interfacial mechanical performance is dependent on the pressure of the interface.…”
Section: -P2mentioning
confidence: 99%
“…Among existing solid substrates, silicon nanostructures (SiNSs) and metal-SiNSs composites are recognized as some of the potential and robust SERS-active substrates because of their admirable properties such as spatial selectivity during physical and chemical treatments, sustainable chemical tunability, surface roughness, earth-abundancy, and compatibility of today’s state-of-the-art technologies and are highly appreciated by the SERS community. , Moreover, these qualities offer the distribution of high-density plasmonic hot-spots across all the spatial planes (i.e., band edges and band gaps), which facilitate the better probability of trap target analytes in the hot-spot regions. Therefore, chemically processed silicon-based NSs show well adaptability in SERS molecular sensing. In the extended view, a comprehensive short review by Wang et al reported extensively on silicon-based SERS substrates for effective SERS sensing .…”
Section: Introductionmentioning
confidence: 99%